A COMPARISON BETWEEN OPTICAL AND RADAR SATELLITE IMAGES FOR DETECTING TROPICAL FOREST FIRES IN SOUTH SUMATRA, INDONESIA - Heri Sunuprapto; Yousif Ali Hussin (Geo Media: Majalah Ilmiah dan Informasi Kegeografian, 2013)
Forest fire in Indonesia is a yearly potential caused for forest degradation. Theinformation available about the main factors that promote the forest fire and informationabout the forest condition after the forest fire are insufficient . This is one of the reasonswhy forest area neglected after they are burned. Remote sensing and GIS are helpful toolsto provide a quick and accurate data acquisition and that can describe the forestcondition after the forest fire. The objectives of this research were to asses the ability ofoptical and radar satellite remotely sensed data to detect, identify and classify forestdamage (burnt area) caused by fire and to develop a spatial model for forest fire hazard.Key words: detection burnt forest, Landsat-TM, ERS, and JERS images